2016
DOI: 10.1128/mbio.00804-16
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Genome Uncoating Requires Ubiquitination

Abstract: The process of genome release or uncoating after viral entry is one of the least-studied steps in the flavivirus life cycle. Flaviviruses are mainly arthropod-borne viruses, including emerging and reemerging pathogens such as dengue, Zika, and West Nile viruses. Currently, dengue virus is one of the most significant human viral pathogens transmitted by mosquitoes and is responsible for about 390 million infections every year around the world. Here, we examined for the first time molecular aspects of dengue vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 34 publications
(44 reference statements)
7
93
0
Order By: Relevance
“…380 Similarly, Byk et al reported that inhibition of E1 enzyme activity blocked DENV uncoating, possibly due to retention of internalized virions in endosomes. 221 This observation supports an earlier study that observed reduced DENV infection due to inhibition of the E1-activating enzyme, UBE1. 381 Another study reported that the E3 ubiquitin ligase, Nedd4, stimulated JEV replication without affecting virus entry, 382 suggesting that the ubiquitin system is important at multiple phases of the flavivirus life cycle.…”
Section: Pro-viral Host Factorssupporting
confidence: 90%
“…380 Similarly, Byk et al reported that inhibition of E1 enzyme activity blocked DENV uncoating, possibly due to retention of internalized virions in endosomes. 221 This observation supports an earlier study that observed reduced DENV infection due to inhibition of the E1-activating enzyme, UBE1. 381 Another study reported that the E3 ubiquitin ligase, Nedd4, stimulated JEV replication without affecting virus entry, 382 suggesting that the ubiquitin system is important at multiple phases of the flavivirus life cycle.…”
Section: Pro-viral Host Factorssupporting
confidence: 90%
“…However, entry and capsid maturation in flaviviruses appear to share a strict requirement for Hsp70 function. The role in entry has not been explored in detail but could in principle be linked to capsid uncoating (Byk et al, 2016; Goodwin et al, 2011). Hsp70 inhibition strongly affects capsid function, reducing its stability (Figure 4B), preventing its association with LDs (Figure 4C), and altering the formation of capsid complexes in the cell (Figure 4F).…”
Section: Discussionmentioning
confidence: 99%
“…The UPS system involves tagging of proteins for enzymatic degradation. Some flaviviruses like Dengue‐2 and Japaneses encephalitis, as well as ZIKV, have been reported to adapt the UPS in their replicative cycles . ISG15 colocalizes with histone deacetylase 6 (HDAC6) and p62 in autophagic degradation of ubiquitinated cellular components .…”
Section: Discussionmentioning
confidence: 99%